CHARACTERISTICS OF RUSSIAN INNOVATIVE ECONOMY - M. S. Krass (Real Economics Publishing House, 2015)
Transition to innovative economy requires creating a number of new characteristics: presence of economic strategy involving infrastructure creation and reorganization; relevant aim multitude; taking legal and economical action in implementing new resource-saving and ecological technologies. Main problems requiring active solution for innovative economy formation are explained.